Mangrove vulnerability and blue carbon storage in the Coral Triangle Areas, Southeast Sulawesi, Indonesia - Analuddin, Kangkuso; Helmi, Muhammad; Pribadi, Rudhi; Adrianto, Luky; Jaya, L. M. Golok; Iba, Wa; Susetyo Adi, Novi; Septiana, Andi; Nadaoka, Kazuo; Nakamura, Takashi (Frontiers in Ecology and Evolution, 2024)
Mangroves play a vital role in the environment and contribute signific aptly to the well-being of coastal communities by providing goods and services. Unfortunately, the degradation and deforestation of mangroves has frequently occurred. Therefore, it is important to understand the vulnerability of mangroves and its impact on blue carbon storage for effective mangrove management and coastal planning. This study aims to assess the vulnerability of mangroves and its effect on blue carbon storage in the coral triangle region of Southeast Sulawesi, Indonesia. The vulnerability assessment included factors such as exposure, sensitivity, and adaptive capacity. Blue carbon storage was evaluated based on carbon stock in sediment, biomass, and total carbon stock in mangrove ecosystems in both protected and unprotected areas. The mangrove ecosystem in the protected area of Rawa Aopa Watumohai National (RAWN) Park showed lower vulnerability due to lower exposure, lower sensitivity, and higher adaptive capacity. On the other hand, mangrove ecosystems in unprotected areas such as Tinanggea (TNG), Kendari Bay (KDI), and Staring Bay (STR) exhibited moderate to high vulnerability due to higher exposure, sensitivity, and lower adaptive capacity. Mangroves in RAWN Park, which were less vulnerable, had higher blue carbon storage in sediment (381.64 tons C/ha), biomass (312.65 tons C/ha), and the entire ecosystem (706.76 tons C/ha). These values were significantly higher (p<0.05) compared to those in TNG (306.66 tons, 144.15 tons, and 448.37 tons C/ha, respectively), KDI (262.08 tons, 227.73 tons, and 470.76 tons C/ha, respectively), and STR (169.44 tons, 66.66 tons, and 253.27 tons C/ha, respectively). The high vulnerability of mangrove ecosystems resulted in reduced carbon storage in the coastal regions of Southeast Sulawesi. Therefore, efforts such as rehabilitation and restoration, legislation, and conservation should be prioritized to enhance blue carbon storage, and other ecosystem services provided by mangroves in the coral triangle region of Southeast Sulawesi.